Managing an elusive force? The Holy Spirit and the anointed articles of Pentecostal prophets in traditional religious Africa - Banda, Collium (Verbum et Ecclesia, 2019)
The use of anointed objects among African Pentecostal prophets as instruments of taping the power of the Holy Spirit is analysed from a perspective of the personality and divinity of the Holy Spirit and the use of magical charms in African traditional religions (ATRs). The main question answered in this article is the following: what does the use of anointed objects among African neo-Pentecostal prophets reveal about the underlying understanding of the Holy Spirit? It is argued that the use of anointed objects to tap into the Spirit's power treats the Spirit as an elusive power that is controlled magically. It is further argued that in Africa, the use of anointed objects resonates with the use of magical charms in ATR. The Christian reliance on anointed objects is challenged by looking at some aspects of the divinity and personality of the Holy Spirit. The significant contribution of the article lies in challenging African Pentecostals to relate to the Holy Spirit as a personal divine being instead of an elusive impersonal force that could be mastered only by anointed objects. Intradisciplinary and/or interdisciplinary implications: This article uses the disciplines of systematic theology, ATRs and biblical theology to analyse the undermining of the personality and divinity of the Holy Spirit among African Pentecostal prophets by their using anointed objects as instruments of conveying the Holy Spirit's presence and power in believer's life and activities.
Free
Keywords: AFRICA; African Pentecostal prophets; African magical charms; DOCTRINAL theology; GODS; HOLY Spirit; Neo-Pentecostal anointed articles; PENTECOSTALISM; PROPHETS; THEOLOGY; neo-Pentecostal icons; the Holy Spirit in Africa